2007
DOI: 10.1007/s10508-007-9276-y
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Callosum Anatomy in Right-Handed Homosexual and Heterosexual Men

Abstract: The results of several studies have shown that homosexual men have an increased prevalence of non-right-handedness and atypical patterns of hemispheric functional asymmetry. Non-right-handedness in men has been associated with increased size of the corpus callosum (CC), particularly of the isthmus, which is the posterior region of the callosal body connecting parietotemporal cortical regions. We hypothesized that isthmal area would be greater in homosexual men, even among right handers. Twelve homosexual and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…Given this unequal distribution and given that information on sexual orientation was unavailable for control subjects, we abstained from conducting analyses for different subtypes. However, a number of previous findings appear to indicate brain-structural alterations associated with sexual orientation (Allen and Gorski, 1992; Byne et al, 2001; LeVay, 1991; Ponseti et al, 2007; Savic and Lindstrom, 2008; Swaab and Hofman, 1990; Witelson et al, 2008). Moreover, a highly controversial line of research has suggested that homosexual and non-homosexual MTF transsexualism are etiologically heterogeneous (Blanchard, 1989a; Blanchard, 1989b), which may be associated with differences in neuroanatomy.…”
Section: Discussionmentioning
confidence: 98%
“…Given this unequal distribution and given that information on sexual orientation was unavailable for control subjects, we abstained from conducting analyses for different subtypes. However, a number of previous findings appear to indicate brain-structural alterations associated with sexual orientation (Allen and Gorski, 1992; Byne et al, 2001; LeVay, 1991; Ponseti et al, 2007; Savic and Lindstrom, 2008; Swaab and Hofman, 1990; Witelson et al, 2008). Moreover, a highly controversial line of research has suggested that homosexual and non-homosexual MTF transsexualism are etiologically heterogeneous (Blanchard, 1989a; Blanchard, 1989b), which may be associated with differences in neuroanatomy.…”
Section: Discussionmentioning
confidence: 98%
“…Heterosexual and homosexual men also have been reported to differ in corpus callosum anatomy, with the isthmus in particular being significantly larger in right-handed homosexual than right-handed heterosexual men 60. Patterns of cerebral asymmetry and functional cortical connectivity also have been linked to sexual orientation in both men and women 61.…”
Section: Sex Differences In the Brainmentioning
confidence: 99%
“…15 The activated region in the anterior cingulate has been related to provoked sadness in normal subjects, and to depressive illness. 15 Witelson et al 16 found that the isthmal area of the corpus callosum was larger in homosexual men and it has been suggested that sexual orientation is associated with callosal anatomy and, by inference, with cognition. Schmahmann 17 suggested that the cerebellum is an essential node in the distributed neural circuitry subserving cognitive functions.…”
Section: Discussionmentioning
confidence: 99%